2017
DOI: 10.1177/1477153517709063
|View full text |Cite
|
Sign up to set email alerts
|

Users’ experiences of lighting controls: A case-study

Abstract: The aim of this paper is to elucidate how occupants perceive their lit environments in a university setting and how they interact with lighting controls using qualitative methods. Semi-structured interviews were carried out with academic teaching and research staff. Thematic analysis identified four main themes: control and choice, connection with the outdoors, concentration and comfort. Participants were largely able to control and adapt their lighting using small power lighting in office spaces and they perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Several studies that apply end-user testing to existing interface design have found that many current products are difficult to understand by users. When light switches are simple and easy to adjust by occupants, users can more easily achieve their preferred light levels [106]- [108]. Interestingly, users are generally very tolerant of their existing lighting configuration, even when they would likely not accept it as a new configuration [107].…”
Section: Rq1: What Influences Behavior?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies that apply end-user testing to existing interface design have found that many current products are difficult to understand by users. When light switches are simple and easy to adjust by occupants, users can more easily achieve their preferred light levels [106]- [108]. Interestingly, users are generally very tolerant of their existing lighting configuration, even when they would likely not accept it as a new configuration [107].…”
Section: Rq1: What Influences Behavior?mentioning
confidence: 99%
“…Someren et al [106] performed interviews with university staff of the lighting of lighting services and identified the lighting of interfaces as one of the largest sources of complaints. The researchers reported multiple usability issues including that light switches are inconsistent between rooms, the majority of light switches fail to meet basic visual impairment and accessibility requirements, the lighting interfaces regularly confused and delayed the building users, and that features such as dimming or zoning were not obvious and where often unknown by users.…”
Section: Rq3: How Can Interface Design and Usability Be Improved To "mentioning
confidence: 99%
“…By applying mixed methods, the findings of this study elucidate how the visual effects related to coziness and visibility play a large role in both the teachers' and students' sense of well-being and comfort. Whereas preferences of lighting scenes have previously been studied in lab-tests [2], this study contributes to the existing field [2,4,5,14] by conducting it in a field-study where daylight is a co-founding factor. In the preliminary study prior to the refurbishment, the light was subconsciously a part of the teachers' everyday practice of the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…In these FG discussions, students were allowed to respond to and build on the comments of other students, which resulted in a similar collection of experiences as those of lecturers. Similar sample sizes for interviews were applied by Van Someren et al (2018) and for FGs by Granito and Santana (2016). The lecturers who were invited to participate in this study were randomly selected out of a list of 42 lecturers who had taught in one of the classrooms described above for at least one year.…”
Section: Selection Of Lecturers and Studentsmentioning
confidence: 99%